THE ROLE OF LINGUISTIC FACTORS IN THE FORMATION OF MASS MEDIA TEXT (Conferencea, 2022)
The purpose of this discourse is to illustrate the importance of mass media, its usage, as well as the word used in the mass media language. Moreover, it illustrates the role of linguistic factors in mass media texts.